Design and evaluation of disposable safety syringes. (2nd April 2016) - Chen, Rain
Abstract : Needle incident had caused many occupational injuries all over the world. Reuse of the syringes also causes many infectious diseases. Many countries are actively promoting the legislation, hoping to use "Single-use Safety Syringe" instead of the traditional syringe. The research puts this theory to the test, author first takes 9 participants form medical filed industrial designers to do Focus Group Interviews and redesign. Next, take the new design test on 98 medical professional. The results indicated disposable syringes (Type III) were significantly better than Type I and Type II syringes in terms of operation time. In addition, 17 evaluative indicators present on SFEF showed Type III scored better on 12 indicators compared to Type I and Type II syringes. Disposable syringes satisfied the latest regulations of the World Health Organization on the safety of syringes and will able to effectively lower the instances of medical personnel needlestick injuries.